(untitled) (American Journal of Islam and Society, 2003)
The Muslim diaspora, which has become established as a significant area of publishing in the past 2 to 3 decades, is being charted by a number of books and journals. This edited collection is a valuable addition to the literature, although specialists in the field will notice some degree of overlap with existing sources. The book is divided into three sections exploring the Muslim experience in America (seven chapters), Europe (three chapters covering France, Germany, and Norway), and areas of European settlement (five chapters covering Australia, New Zealand, South Africa, and the Caribbean). The best way to view this book is to consider it a series of case studies examining how Muslims in different contexts have moved from being tempo rary and peripheral individual sojourners to being, within their adopted societies, generally well-established communities that have largely overcome their internal differences and external structural barriers in order to be publicly recognized as a part of multicultural and multi faith communities and societies. Many of the contributors believe that Muslim minorities are growing, dynamic, confident, and demographically "young" in most of their new societies, and that wherever they have established themselves, they have sustained their presence and thrived, sometimes in the face of extreme hostility. This case study character has advantages and disadvantages. On the one hand, this reviewer found it extremely valuable to learn more about the experience of some very specific minority groups, such as Sahelians in France, who are usually ignored and overshadowed in the literature by the overwhelming Algerian-Moroccan presence in France. Likewise, with relatively little academic material available on Muslims in New Zealand, for example, this book fills many of the academic gaps in the literature. The first-hand accounts from previously unpublished sources were similarly valuable, and the chapter on establishing the Islamic Party in North America constitutes an important documentary record. On the other hand, some chapters went over well-established ground, such as Turks in Germany. Specialists on Muslim minorities will find that some chapters repeat already well-known data and profiles oflslam in these contexts ...